(untitled) (مجلة ديالى للبحوث الانسانية, 2023)
The theme of deportation has shaped the works of many writers, because the current era is the era of immigration, political crises, and wars in which people are forced to leave their countries. Those deportees include those people who leave seemingly of their own accord but really because of circumstances beyond their control. This research reveals an insight into the psychological consequences of the experience of deportation, from psychopolitical point of view, for psychology goes hand in hand in explaining the intractable conflicts, caused by wars, immigration, exile, and deportation. Psychologists turn political, social, and moral issues into empirical ones; they use psychology as a mirror for understanding politics, and the effect of politics on individuals. This research examines the Iraqi contemporary novel Ali Bader’s The Tobacco Keeper (2011), it proves the fact that political events have repercussions in the lives of people who are not directly involved in any political conflicts, but were irrevocably hit by their consequences.